EFFECTS OF THE AIR FLOW ON THE DYNAMIC OF PARTICLES IN THE CIRCULATING FLUIDIZED BED BOILER USING CFD SIMULATIONS - Dariyus, Asyari; Indra Siswantara, Ahmad; Sugiyanto, Didik; Susanto, Herry; R. Gunadi, Gun Gun; Pujowidodo, Hariyotejo; Damis Widiawaty, Candra; Nopryandi; Ardi Wiradinata, Trisna (Jurnal Sains & Teknologi Fakultas Teknik Universitas Darma Persada, 2022)
The optimum distribution of solid phase in fluidized bed system is important thing among others to achieve the best performance. One of the parameter that influences the distribution of solid is air mass flow rate. In this study, simulations of Computational Fluid Dynamics (CFD) is done where Eulerian model is used for solid particle motions and k-εturbulence model for fluid flows. The simulations were carried out using six different air mass flow rates based on the excess air of the reactions. The air mass flow rate influenced the distribution and the velocity of solid phase, and also the pressure difference of gas inside the boiler. The results showed that the excess air between 10 %– 20 % gave the optimum results.